2018
DOI: 10.3390/economies6030040
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Fertility Variation in Rural Communities: The Role of Electricity in Ghana

Abstract: Abstract:We believe the massive rural electrification, which began in 1992, played a significant role in the varying fertility rates across rural Ghana. Rural households with electricity, tend to have fewer children ever born to a woman than households without electricity. Using control function regressions, we identify the contribution of electrification to the rural-rural variation in fertility by exploiting the exogenous variations in the access rate to electricity at the district-level. Our results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…One of them was Samad and Zhang (2017), which evaluated different levels of electricity availability in the context of RERED Programme in Bangladesh which also had a technical support and affordability component. Lee (2019), Kurata (2018), Kumar (2018), Koima (2019), Khandker (2014), Khandker (2013), Fuji (2018, Ding (2018), , Chen (2019), , Chakravorty (2014), Blimpo (2018), Bezerra (2017), Bernard (2014), Bensch (2015), Bensch (2012), Barron (2017), Arráiz (2015), Alcazar (2007), Akpandjar (2018), Akpandjar (2017), Aevarsdottir (2017), Adusah-Poku (2019).…”
Section: Figure 6: Distribution Of Included Studies By Intervention Typementioning
confidence: 99%
See 1 more Smart Citation
“…One of them was Samad and Zhang (2017), which evaluated different levels of electricity availability in the context of RERED Programme in Bangladesh which also had a technical support and affordability component. Lee (2019), Kurata (2018), Kumar (2018), Koima (2019), Khandker (2014), Khandker (2013), Fuji (2018, Ding (2018), , Chen (2019), , Chakravorty (2014), Blimpo (2018), Bezerra (2017), Bernard (2014), Bensch (2015), Bensch (2012), Barron (2017), Arráiz (2015), Alcazar (2007), Akpandjar (2018), Akpandjar (2017), Aevarsdottir (2017), Adusah-Poku (2019).…”
Section: Figure 6: Distribution Of Included Studies By Intervention Typementioning
confidence: 99%
“…Akpandjar (2018) found that electrification contributed to a significant fall in fertility among rural women by between one and three children.…”
mentioning
confidence: 99%
“…Rural areas had higher odds of fertility status as compared to urban areas. The nding was supported by a study conducted in Ghana and another sub-Saharan Africa [15,16]. This could explain by in place of residence, evidence suggests that limited access to family planning and reproductive health information in rural areas and services contributes to these outcomes and rural residents desiring additional children [17].…”
Section: Discussionmentioning
confidence: 81%
“…The NR tend to share similar causes of low use of FP coupled with other factors like poverty, low education among women and religious/cultural beliefs (Akpandjar, Puozaa, & Quartey, 2018). The population Council is supporting Government of Ghana in reaching its Millennium Development Goals (MDG) 5, which is to improve maternal health by 2015, with much focus on reducing maternal morbidity and mortality due to unsafe abortion by improving access to contraceptive services (Novignon, Djossou, & Enemark, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Worldwide, 70 million unwanted pregnancies occur every year; with 20 million resulting in unsafe abortion which contributes to 13% of all maternal mortality (Akpandjar, 2018). An estimated 358,000 maternal deaths occurred worldwide in 2018 with developing countries accounting for 95% of all the deaths.…”
Section: A R T I C L E I N F O Abstract Article Historymentioning
confidence: 99%